Microglia Increase Inflammatory Responses in iPSC-Derived Human BrainSpheres - Abreu, Celina Monteiro; Gama, Lucio; Krasemann, Susanne; Chesnut, Megan; Odwin-Dacosta, Shelly; Hogberg, Helena T.; Hartung, Thomas; Pamies, David (Frontiers in Microbiology, 2018)
Human induced pluripotent stem cells (iPSCs), together with 21st century cell culture methods, have the potential to better model human physiology, with applications in toxicology, disease modeling, and the study of host-pathogen interactions. Several models of the human brain have been developed recently, demonstrating cell-cell interactions of multiple cell types with physiologically relevant 3D structures. Most current models, however, lack the ability to represent the inflammatory response in the brain because they do not include a microglial cell population. Microglia, the resident immunocompetent phagocytes in the central nervous system (CNS), are not only important in the inflammatory response and pathogenesis; they also function in normal brain development, strengthen neuronal connections through synaptic pruning, and are involved in oligodendrocyte and neuronal survival. Here, we have successfully introduced a population of human microglia into 3D human iPSC-derived brain spheres (BrainSphers, BS) through co-culturing cells of the Immortalized Human Microglia - SV40 cell line with the BS model (µBS). We detected an inflammatory response to lipopolysaccharides (LPS) and flavivirus infection elicited in the model when microglial cells are present. A concentration of 20 ng/ml of LPS increased gene expression of the inflammatory cytokine interleukin-6 (IL-6), IL-10, and IL-1β, with maximum expression at 6-12 hours post-exposure. Following infection with Zika and Dengue Virus, increased expression of the IL-6, IL-1β, tumor necrosis factor alpha (TNF-α), and chemokine (C-C motif) ligand 2 (CCL2) genes was observed in BS with microglia, suggesting stronger inflammatory effects in the model when microglia were present than when only astrocyte, oligodendrocyte, and neuronal populations were represented. In addition, cell death following viral infection increased in BS with microglia compared to BS without microglia. These findings suggest that the BS model has potential applications as a physiologically relevant model in infectious disease and host-pathogen interaction research.